Religion in consumer behavior research: the significance of religious commitment and religious affiliation - Abu-Alhaija, Ahmad Saif-Alddin (IJECM Pub UK, 2018)
This study discusses the influence of religion on customers’ attitudes and behaviors mainly through religiosity and religious affiliation as important religious factors can provide a further understanding to existing research models. The challenges and limitations of religiosity and religious affiliation have also been deliberated. This study highlights the significance of describing and understanding the religious influences in terms of a specific religion as this procedure may assist in recognizing the real and deep influences of religion. It was advised that proper religious measurements be developed based on the research settings and goals. Researchers are directed to properly operationalize the religiosity construct in order to measure its influences consistently. The study concludes that researchers should integrate the religious influences (e.g. religiosity) into different models of customer’s attitudes and behaviors. This integration might help marketing practitioners in designing convenient strategies and tactics based on the significance of religion. The present paper serves as a basis of future researches on the religiosity significance and measurements.